2018
DOI: 10.1021/jacs.8b10564
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Electrophilic Nitrogen Source for the Synthesis of Chiral Primary Amines by Copper-Catalyzed Hydroamination

Abstract: A mild and practical method for the catalytic installation of the amino group across alkenes and alkynes has long been recognized as a significant challenge in synthetic chemistry. As the direct hydroamination of olefins using ammonia requires harsh conditions, the development of suitable electrophilic aminating reagents for formal hydroamination methods is of importance. Herein, we describe the use of 1,2-benzisoxazole as a practical electrophilic primary amine source. Using this heterocycle as a new amino gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
56
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 53 publications
1
56
0
Order By: Relevance
“…Vinyl-substituted heteroarenes are challenging substrates and very limited examples were reported by the Buchwald group using 1,2benzisoxazole as electrophilic amine source. 17 We found that nitrogen-containing substrates proved to be poor starting materials for the hydroamination and only low to moderate reactivities and enantioselectivities were observed (3i, 3j). To our delight, our catalytic system was able to accommodate oxygen-and sulfur-bearing substrates including 5-vinylbenzofuran(3g) and 5-vinylbenzo[b]thiophene (3h).…”
mentioning
confidence: 83%
“…Vinyl-substituted heteroarenes are challenging substrates and very limited examples were reported by the Buchwald group using 1,2benzisoxazole as electrophilic amine source. 17 We found that nitrogen-containing substrates proved to be poor starting materials for the hydroamination and only low to moderate reactivities and enantioselectivities were observed (3i, 3j). To our delight, our catalytic system was able to accommodate oxygen-and sulfur-bearing substrates including 5-vinylbenzofuran(3g) and 5-vinylbenzo[b]thiophene (3h).…”
mentioning
confidence: 83%
“…and PPh 3 in catalytic amounts to the reaction medium . The employment of 1,2‐benzisoxazole as electrophilic amine partner equivalent to ammonia affords a practical access to enantioenriched α‐branched and linear primary amines under mild reaction conditions (Scheme ) . The chiral Schiff bases products obtained through this procedure can be quantatively converted into the corresponding primary amines without enantiomeric excess erosion.…”
Section: Alkene Activation Pathwaysmentioning
confidence: 99%
“…[5] We report a CuH-catalyzed hydroamination protocol for enantioselective synthesis of b-amino acid derivatives. This method employs readily available a,b-unsaturated carbonyl compounds with commercially available 1,2-benzisoxazole as an electrophilic primary aminating reagent [9] (Scheme 1 A). In addition, the reaction proceeds through the hydrocupration of a,b-unsaturated carbonyl compounds with the opposite regioselectivity than would be expected based on previous research on CuH-catalyzed hydrofunctionalization reactions.…”
mentioning
confidence: 99%
“…We began our studies by examining the reaction of tertbutyl cinnamate (1 a) under previously reported conditions for asymmetric synthesis of primary amines. [9] Initially, we expected that the copper enolate generated from the aselective hydrocupration of tert-butyl cinnamate (1 a) could react with 1,2-benzisoxazole to afford the a-amino acid derivative 3 a'. However, we found that reactions using several bisphosphine ligands, L1-L4, furnished the reduced alkene 3 a'' as the major product (blue pathway, Table 1, Entries 1-4).…”
mentioning
confidence: 99%
See 1 more Smart Citation